Dow Chemical Company Texas Division plant - Dow Chemical Company (1952)
General view of an unidentified employee at work in the Dow Chemical Company Texas Division plant located in Freeport, Texas. A range of products and processes were researched, developed, and produced at the plant, including chlorination, phenol, and magnesium.
Keywords: Employees; Industries; Dow Chemical Company